A case of an SMA child with a unique clinical and radiological manifestation - Taib, Mai Nurul Ashikin; Sivapunniam, Selva Kumar; Sharifudin, Mohd Ariff; Abdul Aziz, Azian (2013)
Spinal muscular atrophy (SMA) is an autosomal recessive disorder with variable clinical severity. It causes degeneration of the anterior horn cells of the spinal cord resulting in progressive muscle weakness. The widely used classification is based on the age of onset and severity of the manifestation. Orthopaedists will see such cases from time to time, mostly referrals for spinal deformity and weakness. We report a case of a 7-year old boy presented with developmental delay and progressive weakness of all four limbs. By the age of 7, he is already crippled and wheelchair bound. Based on the age of onset, a diagnosis of SMA type II was made. However, the profound weakness and severity of the manifestation were not normally seen in a SMA type II. MRI findings of blunted conus medullaris and dysplastic sacral vertebrae were also not consistent with the diagnosis. Details of the radiological findings are described. The orthopaedic aspects of SMA, rehabilitation in particular, are further discussed.